Thermal Effects and Structural Changes of Photosynthetic Reaction Centers Characterized by Wide Frequency Band Hydrophone Effects of Carotenoids and Terbutryn - Nagy László; Kiss Vladimir; Brumfeld Vlad; Osvay Károly; Börzsönyi Ádám; Magyar Melinda; Szabó Tibor; Dorogi Márta; Malkin Shmuel (2015)
Photothermal characteristics and light-induced structural (volume) changes of carotenoid-containing and noncontaining photosynthetic reaction centers (RCs) were investigated by wide frequency band hydrophone. We found that the presence of carotenoid either does not play considerable role in the light-induced conformational movements, or these rearrangements are too slow for inducing a photoacoustic (PA) signal. The kinetic component with a few tens of microseconds, exhibited by the carotenoid-less RCs, appears to be similar to that of triplet state lifetimes, identified by other methods. The binding of terbutryn to the acceptor side is shown to affect the dynamics of the RC. Our results do not confirm large displacements or volume changes induced by the charge movements and by the charge relaxation processes in the RCs in few hundreds of microseconds time scale that accompanies the electron transfer between the primary and secondary electron acceptor quinones.
Keywords: Fizikai tudományok; Biológiai tudományok